2014
DOI: 10.1111/ajt.12750
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Donor-Specific HLA Antibodies: Biomarkers of Pancreas Transplant Failure

Abstract: This study assesses the role of posttransplant HLA antibody monitoring in the surveillance of pancreas transplant recipients. Four hundred thirty‐three pancreas transplants were performed at the Oxford Transplant Centre 2006–2011 (317 simultaneous pancreas kidney [SPK] and 116 isolated pancreas [IP]). HLA antibody monitoring was performed at 0, 6 and 12 months and annually and during clinical events. There was no association between pancreas graft failure and recipient or donor characteristics. Posttransplant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 28 publications
4
49
2
1
Order By: Relevance
“…Our findings parallel the observations of other groups (21,24,25,31,32) that HLA matching has little impact on overall outcome. Other studies have shown some increased risk for graft loss after AR episodes (33), but only when AR occurs during specific time periods post- transplantation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings parallel the observations of other groups (21,24,25,31,32) that HLA matching has little impact on overall outcome. Other studies have shown some increased risk for graft loss after AR episodes (33), but only when AR occurs during specific time periods post- transplantation.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, a study published that same year involving > 1000 pancreas recipients from earlier eras at our institution showed no difference in graft survival for SPK recipients with HLA-A or -B matching, but did note a trend toward significance with HLA-DR matching (19). Even more recently, multiple studies have shown no difference in graft survival with overall HLA matching when comparing a high number of MMs versus a low number or none (20)(21)(22)(23)(24)(25). Nonetheless, despite no increase in early graft loss, an increased number of MMs does appear to be associated with an increased AR rate (20,21,25).…”
Section: Discussionmentioning
confidence: 85%
“…Analyzing a cohort of 49 pancreatic islet graft recipients, we observed that, although these patients can generate Abs against donor-specific HLA molecules, DSA appearance did not correlate with shortened survival time of the islet grafts. This finding is in striking contradiction with the situation of solid organ transplantation (9, 10), including pancreas transplantation (32,33), for which DSA-mediated rejection is unanimously recognized as the first cause of graft failure.…”
Section: Discussioncontrasting
confidence: 66%
“…Recent work on large pancreas transplant cohorts has shown that the development of DSA after pancreas transplantation is associated with a significantly reduced graft survival, compared to recipients who do not develop DSA [110][111][112][113]. The magnitude of the effect is greatest for recipients of solitary pancreas transplants, with one study showing one-year graft survival of 50% compared to 82.9% where DSA were not present, with survival falling further to 16.7% at 3 years compared to 79.4% in recipients without DSA (p = 0.001) [110].…”
Section: The Role Of Antibodies To Donor Human Leukocyte Antigens (Hlmentioning
confidence: 99%
“…The magnitude of the effect is greatest for recipients of solitary pancreas transplants, with one study showing one-year graft survival of 50% compared to 82.9% where DSA were not present, with survival falling further to 16.7% at 3 years compared to 79.4% in recipients without DSA (p = 0.001) [110]. For combined kidney and pancreas transplants the three-year graft survival without DSA was 90.3%, compared to 71.8% in recipients who developed DSA (p = 0.002) [110]. The degree of HLA mismatch or the presence of non-donor HLA antibodies prior to transplantation do not appear to affect graft survival [110].…”
Section: The Role Of Antibodies To Donor Human Leukocyte Antigens (Hlmentioning
confidence: 99%